18F-FDG PET/CT may detect early response to Imatinib mesylate in GISTs with exon 11 mutation: case report and critical review of literature. Issue 1 (2013) - Musto, A; Chondrogiannis, S; Ferretti, A; Crepaldi, G; Marzola, MC; Rampin, L; Pasini, F; Rubello, D
No abstract available